Integration of Renewable Energy Education in the Paradigm of Harmony and Sustainability: A Systematic Literature Study - Arianto, Erwin; Yoku, Rosdiana; Islamiati, Desy; Chamami, M Rikza (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
This research aims to analyze the integration of renewable energy education in the paradigm of harmony and sustainability through conceptual and empirical studies that develop in the academic literature. This type of research is a systematic literature study with a search of scientific articles in reputable databases published in the range of 2015–2025. A total of 17 articles that met the inclusion criteria were analyzed to identify approaches, integration models, and their implications for the formation of ecological and sustainability awareness. The analysis technique used is content analysis to categorize themes, curriculum integration patterns, pedagogical strategies, and value orientation that support harmony between humans, the environment, and clean energy technology. The results of the analysis show that the integration of renewable energy education is effective when implemented in an interdisciplinary, project-based, and contextual manner with sustainability values, so as to be able to increase energy literacy, pro-environmental attitudes, and social responsibility of students. The focus of the scientific contribution of this research is to offer an integrative conceptual framework that places renewable energy education as a strategic instrument in building a paradigm of ecological harmony and sustainable development in the education sector. These findings are expected to be a reference for the development of education curricula and policies that are responsive to the challenges of the global energy and environmental crisis.